Trade and qualification: Linking qualification needs to Germany's export flows - Anke Mönnig; Gerd Zika; Tobias Maier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
Foreign markets determine success and failure of those industries that have become reliant on foreign demand, impair the demand for employment and invoke changes in occupational fields and qualification requirements. This paper aims to disclose the direct and indirect influence of major trading partners on Germany's production, employment, and qualification needs. It projects the effects by using the dynamic macroeconometric input-output model INFORGE. Industrialised econo-mies are the most important determinants for employment in the manufacturing industries. Businessrelated services are highly indirectly affected. The growth impact of industrialised nations is declining while BRICS nations are gaining momentum. A shift towards higher qualification needs can be observed. – – Ausländische Märkte bestimmen über Erfolg oder Misserfolg von Branchen, die von der Auslandsnachfrage abhängig geworden sind, beeinträchtigen die Arbeitsnachfrage und verändern Berufs- und Qualifikationsanforderungen. Dieses Papier unter-sucht die direkten und indirekten Einflüsse der wichtigsten Handelspartner auf die Produktion, die Beschäftigung und den Qualifikationsbedarf in Deutschland. Zur Quantifizierung dieser Effekte wird das dynamische makro-ökonometrische Input-Output-Modell IAB/INFORGE verwendet. Die hochentwickelten Industrieländer sind die wichtigsten Determinanten für die Beschäftigung im Verarbeitenden Gewerbe. Unternehmensbezogene Dienstleistungen sind nur indirekt betroffen. Das Wachstum der Industrienationen ist jedoch rückläufig, während die BRICS Staaten an Dynamik gewinnen. Eine Verschiebung hin zu höheren Qualifikationsanforderungen konnte beobachtet werden.
Keywords: F16; F17; F14; 330; projection; labour demand; occupational field; qualification level; international trade; input-output analysis